2022
DOI: 10.1101/2022.04.01.22273107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 in standardised First Few X cases and household transmission investigations: a systematic review and meta-analysis

Abstract: First Few X cases (FFX) investigations and Household transmission investigations (HHTI) are essential epidemiological tools for early characterisation of novel infectious pathogens and their variants. We aimed to estimate the household secondary infection attack rate (hSAR) of SARS-CoV-2 in investigations aligned with the WHO Unity Studies HHTI protocol. We conducted a systematic review and meta-analysis according to PRISMA 2020 guidelines (PROSPERO registration: CRD42021260065). We searched Medline, Embase,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Household transmission has played a significant role in the scale of the COVID-19 pandemic [21,24]. There is a lack of conclusive evidence on the impact of vaccines to prevent secondary infections in household contacts; some studies have demonstrated a positive impact of COVID-19 vaccines on reducing household transmission of SARS-CoV-2 [12][13][14][15][16] while others reported limited impact in decreasing the risk of household transmission of COVID-19 especially for contacts of Delta variant index cases [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Household transmission has played a significant role in the scale of the COVID-19 pandemic [21,24]. There is a lack of conclusive evidence on the impact of vaccines to prevent secondary infections in household contacts; some studies have demonstrated a positive impact of COVID-19 vaccines on reducing household transmission of SARS-CoV-2 [12][13][14][15][16] while others reported limited impact in decreasing the risk of household transmission of COVID-19 especially for contacts of Delta variant index cases [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic in the absence F I G U R E 2 A practical example. In the transmission of SARS-CoV-2 in standardised first few X cases and household transmission investigations: a systematic review and meta-analysis, 8 teams of two investigators critically appraised a total 80 studies eligible to be included in the systematic review. of a fit-for-purpose critical appraisal tool, generic tools for longitudinal studies, 10,11 which do not adequately capture the nuances of HHTIs, were used or partially adapted.…”
Section: The Hhti Critical Appraisal Checklistmentioning
confidence: 99%
“…Further, as stated in the Unity Studies HHTI protocol, investigators may need to adapt HHTIs to local circumstances—including public health mandates, laboratory and health system capacity, financial resources, sociopolitical context, and culture‐specific household practices 5 . Such adaptations lead to heterogeneity in implementation 7,8 . For example, many HHTIs for COVID‐19 conducted throughout 2020 and 2021 8,9 were adapted to local context but not clearly reported 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations